Accounting Discretion, Horizon Problem, and CEO Retirement Benefits - Kalyta, Paul (The Accounting Review, 2009)
ABSTRACT: Empirical research on the impact of managerial retirement on discretionary accounting choices is inconclusive, with most studies finding no evidence of earnings management in the pre-retirement period. I argue that income-increasing accounting choices in final pre-retirement years are particularly appealing to managers whose pension depends on firm performance in these years. Using primary data on retired CEOs of Fortune 1000 firms, I investigate the impact of CEO pension plans on discretionary accruals. Consistent with the prediction, I find evidence of income-increasing earnings management in the pre-retirement period only when CEO pension is based on firm performance. I also report evidence of negative abnormal market reaction to CEO retirement in firms with performance-contingent CEO pensions.